2018
DOI: 10.1016/j.jpsychires.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Delayed unpaired extinction as a treatment for hyperarousal of the rabbit nictitating membrane response and its implications for treating PTSD

Abstract: Treatment for PTSD (Post-traumatic stress disorder) is rarely available immediately after trauma and often delayed for weeks or months after an event. In a rabbit eyeblink conditioning model of PTSD, we have previously shown that presentations of a tone conditioned stimulus (CS) and shock unconditioned stimulus (US) in an explicitly unpaired manner known as unpaired extinction is effective in reducing CS responding and US hyperarousal even if shock intensity is reduced eight-fold and elicits only minimal respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 58 publications
(71 reference statements)
1
2
1
Order By: Relevance
“…Of note, in this study we did not find a significant reduction in the size of CRM following extinction treatment in muscimol rabbits nor in saline controls, despite several previous publications demonstrating that six days of unpaired extinction with weak shock induces significant decreases in amplitude and area of CRM (Burhans et al, 2015, 2018; Schreurs et al, 2011, 2018). Because we typically see a fair degree of variability in terms of individual responsiveness to extinction treatment, it may be that by chance, we had more extinction-resistant subjects in this cohort.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…Of note, in this study we did not find a significant reduction in the size of CRM following extinction treatment in muscimol rabbits nor in saline controls, despite several previous publications demonstrating that six days of unpaired extinction with weak shock induces significant decreases in amplitude and area of CRM (Burhans et al, 2015, 2018; Schreurs et al, 2011, 2018). Because we typically see a fair degree of variability in terms of individual responsiveness to extinction treatment, it may be that by chance, we had more extinction-resistant subjects in this cohort.…”
Section: Discussioncontrasting
confidence: 96%
“…The current study has confirmed, however, that IP is not needed to extinguish CRM timing, and it's important to note that all aspects of CRM, including the latency increase, do not simply fade with the passage of time, persisting for at least a month following conditioning (Schreurs et al, 2018). Therefore, the extinction of CRM is likely an active process with distinct neural substrates.…”
Section: Possible Cerebellar Mechanisms For Associative Timing Change...supporting
confidence: 66%
See 2 more Smart Citations